Tác động gián tiếp của quản trị nguồn nhân lực định hướng trách nhiệm xã hội đến kết quả làm việc của người lao động thông qua cam kết tổ chức - Nguyễn Minh, Cảnh; Phạm Thái, Bảo; Ong Quốc, Cường; Châu Thị Lệ , Duyên; Nguyễn Thị Phương, Dung; Lê Thị Tú, Quyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study analyzes the indirect impact of socially responsible human resource management (SRHRM) on employee task performance through their organizational commitment. The research model is built on the basis of social identity and person-organization fit theories. The structural equation modeling (SEM) was used to test the research hypotheses with the survey data of 360 employees working at enterprises in Can Tho city. The analysis results show that SRHRM has a positive effect on all 3 components of organizational commitment (e.g., affective commitment, normative commitment, and continuance commitment). In addition, affective commitment and normative commitment have a positive effect on employee task performance, however, continuance commitment and employee task performance are not correlated. The research results also show that SRHRM has an indirect impact on employee task performance via affective commitment and normative commitment. Based on the research findings, managerial implications to improve employee performance via SRHRM implementation are discussed.
Keywords: Human resource management; Corporate social responsibility; Task performance; Structural equation modeling